MODERNIZATION OF TAX CONTROL UNDER THE DIGITALIZATION OF THE ECONOMY (E Conference Zone, 2022)
The article discusses the history of the spread of information and communication technologies and the impact on the tax policy of the country. In connection with the development of telecommunications information technologies, the interaction between companies, buyers and sellers has become simpler, the business process has become more open, and the ability of organizations to buy and sell goods and services has expanded significantly.